Topology and the Sociological Imagination in the Theatrical Performance (Technical Approach in the Theatre of Pina Bausch) (Journal of the College of Basic Education, 2022)
Going into the midst of theatrical experiences is delving into all human experiences, according to their intellectual, artistic, aesthetic and technical data, and the art of theatre is a branch of sciences like the rest branches, as it draws from, gives and interacts with them, and it is in constant renewal as long as life and its indicators are renewing, whether for better or worse.This research is determined by studying (topology and the sociological imagination in the theatrical performance - a technical approach in the Theatre of Pina Bausch). In his analysis of the sample, the researcher dealt with an intentional theatrical presentation from the performances of the German director and choreographer (Pina Bausch), which was presented in (2008) at the theatres of Paris, that dealt with The effect of place on the sociological imagination in addressing the dramatic space of the performance, and the focus on the technical approach between employing topology and the sociological imagination in the theatrical performance.The research focused on the centre of the problem represented by the question of what is topology, sociological imagination and their impact on the structure of the theatrical performance.As (the researcher) attempted to reach solutions for that problem by revealing those relationships and parallels between topology and the sociological imagination in the composition of the elements of the presentation and the structure of the visual image of the theatrical space by using scenography related to the performance of the actor in the space and his work on the rest of the elements of theatrical production.